2014
DOI: 10.1186/s12913-014-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators of health systems change for tobacco dependence treatment: a qualitative study of stakeholders? perceptions

Abstract: BackgroundHealth systems play key roles in identifying tobacco users and providing evidence-based care to help them quit. Health systems change – changes to health care processes, policies and financing – has potential to build capacity within these systems to address tobacco use. In 2010, ClearWay MinnesotaSM piloted a health systems change funding initiative, providing resources and technical assistance to four health care systems. This paper presents findings from a process evaluation, describing key stakeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Consistent with an existing qualitative study of organisational change in healthcare settings [19], which shows the importance of an influential and current employee, staff reported that a support champion was essential to ensuring the successful maintenance of the intervention. Effective support champions are not those who just implement the intervention but serve as a local expert [20].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Consistent with an existing qualitative study of organisational change in healthcare settings [19], which shows the importance of an influential and current employee, staff reported that a support champion was essential to ensuring the successful maintenance of the intervention. Effective support champions are not those who just implement the intervention but serve as a local expert [20].…”
Section: Discussionsupporting
confidence: 61%
“…Drawing upon the healthcare reform literature [21], suggested strategies to address barriers, such as a lack of employee engagement, involve specific drivers: Staff are involved in the decision-making, the facility provides encouragement for development, and two-way dialogue with facility leaders and co-workers to create a reliable support team [22]. Providing these opportunities in an effort to address barriers, such as lack of engagement, will allow for services to efficiently implement the new processes and procedures within their setting [19].…”
Section: Discussionmentioning
confidence: 99%
“…The Health Systems Change Partnerships program was informed by Clinical Practice Guidelines for Treating Tobacco Use and Dependence and similar work in other communities. 19,22,23 The initiative's central focus was to leverage partnerships to support health systems in building capacity to develop system-level solutions to facilitate clinicians in consistently and effectively addressing tobacco use among their patients. Participating health care organizations were expected to develop systems change initiatives that focused on 3 areas: implementing best practices for tobacco dependence treatment; quality improvement; and utilization of an EHR system.…”
Section: Program Descriptionmentioning
confidence: 99%
“…[ 22 23 ] One study conducted in Minnesota showed that health systems also determine the tobacco use screening by physicians. [ 24 ] Electronic health records or paper documentation of tobacco use status, availability of nicotine gums/patches in pharmacy, training and education of staff, referral to tobacco cessation professionals, were some simple measures that facilitated tobacco use screening and treatment of patients. [ 24 ] Few studies have shown a correlation between present illness of patient and tobacco use screening by healthcare provider.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] Electronic health records or paper documentation of tobacco use status, availability of nicotine gums/patches in pharmacy, training and education of staff, referral to tobacco cessation professionals, were some simple measures that facilitated tobacco use screening and treatment of patients. [ 24 ] Few studies have shown a correlation between present illness of patient and tobacco use screening by healthcare provider. According to one study conducted in two Indian states (Andhra Pradesh and Gujarat), patients with respiratory illness were more likely to be screened for tobacco use by healthcare provider as compared to patients with general ailments.…”
Section: Discussionmentioning
confidence: 99%